Molecular study to detect cutaneous leishmania with identify the parasite species and screening for some virulence factors own - Sahib, Rana Salih; Jassem, Ghyda,a Abbas (Al-Qadisiyah Journal of Pure Science, 2017)
This study aimed to evalute the sensitivity of the polymerase chain reaction technique (PCR) in detection of cutaneous leishmania parasite ,and identification the species of parasite,with search for the presence of three virulence factors lipophosphoglycan, Cysteine protease and proteophosphoglycans by using the same technique .Fifty-five biopsies were taken from skin ulcers which clinically diagnosed as cutaneous leishmaniasis from patients attending education AL-Diwaniyah hospital in AL-Qadisiya city for the period between 1 11 2012-1 5 2013 ,whose age ranged from (10-80) years .The DNA was extracted from samples,then amplified by using primers selected on repetitive kDNA for identification of a Leishmania parasite, it is L.major species and the above three virulence factors,after that DNA electrophoresis was done for the amplified DNA. The results showed that Leishmania parasite was detected in 89.09% of samples.The L.major species was identified in the majority of Leishmania parasite positive samples 98%. And the above three virulence factors were identifed in all L.major positive samples.There for , the study confirmed that PCR technique is a sensitive method in diagnosis of cutaneous leishmaniasis .Beside that it can be use in differentiation among different cutaneous leishmania spp. And identification of some parasite virulence factors. The study showed the L.major is the main cutaneous leishmania species in AL-Qadisiya city beside the prrsence of the three virulence factors in all L.major samples.